Influence of theophylline on cleavage rate and embryonic development following in vitro fertilization of buffalo oocytes - Chauhan, M S; Singla, S K; Palta, P; Manik, R S; Madan, M L (The Indian Journal of Animal Sciences, 2012)
In vitro matured buffalo cumllius-oocyte-complexes were subjected to in vitro fertilization (IVF) with spermatozoa treated with 5 mM caffeine or theophylline. The fertilized oocytes were co-cultured with buffalo oviductal epithelial cells for 9 days. Theophylline increased post-fertilization cleavage rate to values similar to those obtained with caffeine (40 and 59% respectively). The proportion of cleaved embryos which developed to morula and blastocyst stage, following use of theophylline (65 and 25% respectively) was also similar to that obtained with caffeine (42 and 34% respectively). These results suggest that theophylline can be used for preparing sperm for IVF and that its efficacy is comparable to that of caffeine in terms of post-fertilization cleavage rotes and subsequent embryonic development.